Pengaruh Resiliensi terhadap Psychological Well-Being dengan Dukungan Sosial sebagai Moderator pada Remaja Putus Sekolah - Auliya, Naila Putri Dita; Eva, Nur; Hidajat, Helga Graciani (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Dropping out of school is a risky behavior that threatens an individual's psychological well-being. Those who drop out of school need social support to help them get back on their feet, overcome problems (resilience), and achieve psychological well-being. This study aims to determine the role of social support as a moderator in the influence of resilience on psychological well-being among school dropouts. This study uses a quantitative approach with a correlational research design. The study population consists of school dropouts currently enrolled in an equivalency education program at the Community Learning Center (PKBM) in Malang City. The sampling technique used multistage sampling, resulting in a sample size of 348 individuals. Data were collected using Ryff’s Psychological Well-being Scale (RPWBS), Connor-Davidson Resilience Scale (CD-RISC), and Multidimensional Scale of Perceived Social Support (MSPSS). Each scale of the three variables was analyzed using confirmatory factor analysis (CFA) to determine validity and reliability. Data analysis in this study was conducted using structural equation modeling (SEM). The results of the structural model test indicated that the interaction between resilience and social support (moderating effect) significantly influenced psychological well-being, with a CR value of 3.244 (>1.96) and a p-value of 0.001 (p < 0.05). This means that out-of-school adolescents with high levels of resilience are more capable of improving their psychological well-being when they also receive strong social support.